Views of 13th Century Arab Travelers on the History of Early Christian Communities - Agzamova, Nozima B. (Indonesian Journal Publisher, 2025)
This study investigates the depictions of Christian communities in the travel accounts of 13th-century Muslim geographers and travelers. The aim is to analyze their geographical spread, religious practices, social conditions, and interfaith relations within the broader Islamic world. Employing a qualitative historical analysis of primary Arabic sources, including works by Yaqut al-Hamawi, Zakariya al-Qazwini, Ibn al-Mujawir, and Abu al-Fida, the research highlights descriptions of Christian communities across the Middle East, East Africa, al-Andalus, and Central Asia. The findings reveal that Arab travelers not only documented Christian places of worship and practices but also emphasized coexistence and cultural plurality. The study concludes that such medieval Arabic sources provide invaluable insights into interreligious dynamics, tolerance, and historical thought in the Islamic world.